2016
DOI: 10.1097/ccm.0000000000001375
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a Modified Sequential Organ Failure Assessment Score Using the Richmond Agitation-Sedation Scale

Abstract: Objective The Sequential Organ Failure Assessment (SOFA) and other severity of illness scales rely on the Glasgow Coma Scale (GCS) to measure acute neurologic dysfunction, but the GCS is unavailable or inconsistently applied in some institutions. The objective of this study was to assess the validity of a modified SOFA that uses the Richmond Agitation-Sedation Scale (RASS) instead of GCS. Design Prospective cohort study Setting Medical and surgical intensive care units within a large, tertiary care hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 35 publications
3
48
0
1
Order By: Relevance
“…The study revealed that there is a statistical significance difference between study and control groups regarding behavioral pain scale before and after sedation study group treatment also there is a statistical difference between groups regarding behavioral pain scale after the third day from sedation treatment discontinuation this disagree with (Rijkenberg, et al, 2015) & (Syan et al, 2017) who mentioned that the behavioral pain scale remained unchanged after using sedation for pain relive patients. The present study demonstrated that there is a statistical significance difference between groups before and during sedation treatment also after sedation treatment cessation regarding behavioral pain scale this agree with (Vasilevskis, et al, 2016) who suggest that pain management guidelines had positive effect on behavioral pain scale.…”
Section: Regarding the Behavioral Pain Scalesupporting
confidence: 91%
“…The study revealed that there is a statistical significance difference between study and control groups regarding behavioral pain scale before and after sedation study group treatment also there is a statistical difference between groups regarding behavioral pain scale after the third day from sedation treatment discontinuation this disagree with (Rijkenberg, et al, 2015) & (Syan et al, 2017) who mentioned that the behavioral pain scale remained unchanged after using sedation for pain relive patients. The present study demonstrated that there is a statistical significance difference between groups before and during sedation treatment also after sedation treatment cessation regarding behavioral pain scale this agree with (Vasilevskis, et al, 2016) who suggest that pain management guidelines had positive effect on behavioral pain scale.…”
Section: Regarding the Behavioral Pain Scalesupporting
confidence: 91%
“…Unfortunately, the overall score performance regarding adverse outcomes was not described. Recently Vasilevskis et al introduced a promising approach substituting the GCS scale by the use of the Richmond Agitation-Sedation Scale (RASS), which is easier to apply in sedated and intubated patients [23, 24]. Although this score has to be validated in a more comprehensive patient cohort including trauma patients, the use of RASS can avoid an underestimation of the SOFA score, which might occur when the neurologic component is ignored [25].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary effects include cerebral hypoxia or metabolic dysregulation in association with failure of pulmonary or other organ systems, such as can be seen in a variety of other types of delirium [6]. Environmental and iatrogenic factors such as prolonged mechanical ventilation, sedatives (especially benzodiazepines), and immobility also contribute heavily to the risk of ICU delirium [7] and can contribute to its development in the context of acute COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%